1991
DOI: 10.1159/000235383
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Dermal and Systemic Application of Glucocorticoids on the RM 3/1<sup>+</sup> Macrophage in Human Blood

Abstract: Dermal administration of either hydrocortisone or fluprednidene to healthy skin causes only a weak and short-lasting increase of the proportion of the anti-inflammatory macrophage RM 3/1 in the blood compared to the effect of the systemic application of glucocorticoids on this cell subtype. On the other hand, a rather permanent increase of these macrophages could be observed in untreated patients suffering from certain skin diseases, e.g. urticaria, atopic dermatitis, psoriasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1996
1996
1998
1998

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…This special responsiveness of psoriatic monocytes to alternative macrophage activators may be another reason why we have found that psoriatic macrophages display an alternatively activated macrophage phenotype. Confirming this notion, expression of the alternative macrophage antigen RM 3/1 has been shown to be considerably elevated on peripheral blood monocytes of a single PSO patient [67].…”
Section: Discussionmentioning
confidence: 66%
“…This special responsiveness of psoriatic monocytes to alternative macrophage activators may be another reason why we have found that psoriatic macrophages display an alternatively activated macrophage phenotype. Confirming this notion, expression of the alternative macrophage antigen RM 3/1 has been shown to be considerably elevated on peripheral blood monocytes of a single PSO patient [67].…”
Section: Discussionmentioning
confidence: 66%
“…Administration of glucocorticoids either intravenously, subcutaneously or dermally but also endogenous cortisol induced by major trauma, e.g. severe burn injuries, cause the formation of RM 3/1 monocytes in blood [5][6][7]14]. Therefore monitoring of the expression of RM 3/1 monocytes was used as a parameter to evaluate the anti-inflammatory efficacy of glucocorticoids.…”
Section: Discussionmentioning
confidence: 99%
“…Using different glucocorticoids and routes of administration, e.g. intravenous, subcutaneous or dermal, so far only dermal application revealed a clearly dose-dependent difference between glucocorticoids [5][6][7].…”
Section: Introductionmentioning
confidence: 99%